Expanded roles of community health workers to sustain malaria services in the Asia-Pacific: A landscaping survey. - Monnaphat Jongdeepaisal; Massaya Sirimatayanant; Panarasri Khonputsa; Phone Si Hein; Laura Buback; Naomi Beyeler; Amita Chebbi; Richard J Maude (PLOS Global Public Health)
Malaria Community Health Workers (CHWs) in the Greater Mekong Subregion (GMS) are an important component of malaria elimination efforts. As malaria declines with intensified efforts to eliminate by 2030, expanding their roles beyond malaria could help to sustain funding and provision of malaria services at the community level. Evidence of how programmes have implemented and managed CHWs performing both malaria and non-malaria roles across the Asia-Pacific region can provide insight into the viability of this strategy. A short survey was distributed to national malaria programmes and implementing organizations in the Asia-Pacific region in 2021-2022. The survey identified CHW programmes in the region, and collected information on malaria and non-malarial services provided by CHWs, characteristics of each identified programme, and the impact of COVID-19 on these programmes. 35 survey responses identified 28 programmes in 14 countries. The most frequently reported services provided by malaria CHWs were health promotion and education for malaria (13/14 countries) and other diseases (11/14); and COVID-19 related activities (10/14). Most programmes were financed wholly through donor funding (18/28 programmes), or donor plus government funding (6/28). Of 21 programmes which performed programme evaluation, only 2 evaluated their impacts on diseases beyond malaria. Declining donor funding, and COVID-19 related travel and activity restrictions were identified as implementation challenges. CHWs across the Asia Pacific provide a range of health services with malaria and are resilient under changing public health landscapes such as the COVID-19 pandemic. Further investigation into the impact of additional roles on malaria CHW performance and targeted health outcomes is needed to verify the benefits and feasibility of role expansion. As the GMS approaches elimination, and funding declines, verifying the cost effectiveness of malaria CHW programmes will be vital to persuade donors and countries to invest in malaria CHWs to sustain malaria services, and strengthen community-based health care.